LEGAL STATUS OF BANK GUARANTEE ON BEHALF OF THIRD PARTIES IN BANKRUPTCY PERSPECTIVE - Hartini, Rahayu (Faculty of Law, Universitas Sebelas Maret, 2017)
This study aimed to observe the legal status of the immovable that became a bank guarantee on behalf of third parties in the bankruptcy and whether the curator has the authority to insert objects that have been done Collateral guarantees which Foreclosed (hereinafter referred AYDA) prior to the bankruptcy decision boedel into bankruptcy.The method used is a normative research using three approaches: statute approach, conceptual approach, case approach, and analyzed